GIS-Based Landslide Susceptibility Mapping Using Overlay and Scoring Techniques Along the Nanggulan–Kalibawang Road, Kulon Progo - Afrinaldi, Rahman; Eryuliana, Rina (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aims to evaluate landslide susceptibility along Nanggulan–Kalibawang road corridor, Kulon Progo, by identifying spatial distribution of vulnerability classes and dominant factors influencing slope instability, providing context-specific information for disaster risk reduction and infrastructure planning.Methodology: GIS-based spatial multi-criteria analysis (SMCA) was applied using ArcGIS 10.8 software. Primary data included slope measurement, soil depth, and laboratory analysis of soil samples. Secondary data consisted of thematic layers of geology, soil type, landform, land use, and vegetation. Weighted overlay and scoring techniques were used to generate landslide susceptibility index.Main Findings: Results indicate moderate to high vulnerability dominates hilly zones along the corridor. Very high susceptibility zones are located on steep slopes with sparse vegetation and intensive land use. Slope gradient and land use are the most dominant factors. Five susceptibility classes, ranging from very low to very high, were delineated providing fine-resolution spatial information for prioritizing mitigation measures.Novelty/Originality of this study: This study introduces corridor-specific landslide susceptibility mapping using integrated overlay and scoring techniques within GIS. Unlike regional assessments, seven terrain parameters are combined into a unified spatial model producing fine-resolution susceptibility zones. Findings provide practical guidance for disaster risk management along strategic road corridors and advance knowledge by offering a replicable framework for localized hazard assessment.